INSTITUSI PENDIDIKAN DALAM TASAWUF - Syamsun Ni’am (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2013)
In history of Islamic education, we know that institution of Islamic education shape and spreading rapidly in the Islamic world since they have emerged. Here we recognize term of pesantren, school and madrasah, what we consider to be institution of Islamic education. However we need to know that in world of sufi sm also there is education institusionalization; and this matter also had experience of growth and played an important role the same well. It is considered to be semy formal education institute, which later called as zawiya, khanaqah, ribath, and tarekat. Here is also arranged by a curriculum, syillaby, educational items, and soon, as going into effect in education world in general. This paper will try to discuss about education institutions which emerge and expand among all sufi , with relevant things.